2021
DOI: 10.3389/fonc.2021.614398
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Prognostic Model for Predicting Lymph Node Metastasis in Early Colorectal Cancer: Analysis Based on the Surveillance, Epidemiology, and End Results Database

Abstract: BackgroundIdentification of a simplified prediction model for lymph node metastasis (LNM) for patients with early colorectal cancer (CRC) is urgently needed to determine treatment and follow-up strategies. Therefore, in this study, we aimed to develop an accurate predictive model for LNM in early CRC.MethodsWe analyzed data from the 2004-2016 Surveillance Epidemiology and End Results database to develop and validate prediction models for LNM. Seven models, namely, logistic regression, XGBoost, k-nearest neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Numerous novel ML algorithms have remedied deficiencies of canonical statistical methods, such as overfitting, unbalanced data distribution and so on. Ji Hyun Ahn et al [ 19 ] developed an innovative model (AUC = 0.96) to predict LNM in the early stage of CRC patients via utilizing the SEER database and adopting seven AI methods. Nevertheless, these studies were retrospective, single-center, and with small quantities of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous novel ML algorithms have remedied deficiencies of canonical statistical methods, such as overfitting, unbalanced data distribution and so on. Ji Hyun Ahn et al [ 19 ] developed an innovative model (AUC = 0.96) to predict LNM in the early stage of CRC patients via utilizing the SEER database and adopting seven AI methods. Nevertheless, these studies were retrospective, single-center, and with small quantities of patients.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that synchronous LM was an independent prognostic factor for CRC patients [12]. Likewise, Ji Hyun Ahn [17] et al have developed an innovative model to predict LNM in the early stage of CRC patients via utilizing the SEER database and adopting seven AI methods. Nevertheless, these studies were retrospective, single-center, and with small quantities of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the depth and breadth of the discipline integration have signi cantly enhanced [14,15]. Researchers have employed machine learning (ML) as the breakpoint to better solve the complicated problem for clinical prediction and acquired several signi cant breakthroughs in CRC [16][17][18]. Given that most of the present studies merely focused on the public database when studying the apparent discrepancy among different populations, limitations ineluctably appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the articles on this topic use machine learning and deep learning approaches for prediction (81 articles), and diagnosis (16 articles). In particular, regarding the prediction approaches, some previous research elaborated the following predictions: patient survival likelihood [86], cancer prognosis [87], treatment plans [88], and metastasis (cancer spreads to a different body part) [89]. And the rest were the predictions of radiation risk in breast cancer [90], mortality risk [91], malignancy (local spreading) [92], and recurrences [93].…”
Section: Miscellaneous Diseasesmentioning
confidence: 99%